2010
DOI: 10.1128/jvi.01190-10
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Specific Neutralization and Protection by Antibodies against Dengue Virus Type 3

Abstract: Dengue viruses (DENV) comprise a family of related positive-strand RNA viruses that infect up to 100 million people annually. Currently, there is no approved vaccine or therapy to prevent infection or diminish disease severity. Protection against DENV is associated with the development of neutralizing antibodies that recognize the viral envelope (E) protein. Here, with the goal of identifying monoclonal antibodies (MAbs) that can function as postexposure therapy, we generated a panel of 82 new MAbs against DEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(162 citation statements)
references
References 65 publications
6
153
2
1
Order By: Relevance
“…121 Recently, evidence of antigenic differences between genotypes of the same serotype has emerged. 122,123 To date these differences have been elucidated using mAbs specific to the E protein and it remains to be seen whether such differences are present in the face of polyclonal immune sera. Prospective cohort studies that can follow the introduction of different DEN virus genotypes into the same population are needed to understand the clinical and epidemiological significance of antigenic variation between DEN virus genotypes.…”
Section: Virus Epidemiology and Virulencementioning
confidence: 99%
“…121 Recently, evidence of antigenic differences between genotypes of the same serotype has emerged. 122,123 To date these differences have been elucidated using mAbs specific to the E protein and it remains to be seen whether such differences are present in the face of polyclonal immune sera. Prospective cohort studies that can follow the introduction of different DEN virus genotypes into the same population are needed to understand the clinical and epidemiological significance of antigenic variation between DEN virus genotypes.…”
Section: Virus Epidemiology and Virulencementioning
confidence: 99%
“…But, it has been demonstrated that dengue neutralization by antibodies could vary up to 10 times among different genotypes of the same serotype, this is one of the hypothesis of the reduced CYD 23 vaccine efficacy and might have an impact on the future of dengue vaccines. 8,17,[24][25][26][27] The prM/E expressed in VSV-DENV-2 belongs to the NGC Asian genotype 2 and the DENV-2 TR1751 used on the neutralization and challenge experiments is an American genotype. Although they belong to different genotypes and share 93% of identity, 28 the immunity raised by VSV-DENV-2 NGC was sufficient to neutralize the heterologous American genotype TR1751 infection in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These genotype-dependent epitopes are JEV-specific and completely different from those of DENV (Bernardo et al, 2009;Brien et al, 2010;Kochel et al, 2002;Shrestha et al, 2010;Wong et al, 2007). Previous studies using mAbs indicated that the potent neutralizing capacity was impacted by the genotype-dependent conformational change/exposure of the CC9 loop epitope in DIII (Austin et al, 2012).…”
Section: Bhk-21 C6/36mentioning
confidence: 99%